The History of Don Quixote, Volume 2, Part 37 - Cervantes Saavedra, Miguel de, 1547-1616; Doré, Gustave, 1832-1883; Ormsby, John, 1829-1895 (Salt Lake City, UT : Project Gutenberg, 2004)
"The History of Don Quixote, Volume 2, Part 37" by Miguel de Cervantes Saavedra is a section of a novel originally published in two parts in 1605 and 1615. This installment continues the adventures of Alonso Quijano, a nobleman driven mad by chivalric romances who becomes the knight-errant Don Quixote. Accompanied by his earthy squire Sancho Panza, Don Quixote navigates a world where illusion and reality blur. As their journey progresses, the idealistic knight descends toward reality while his pragmatic companion ascends toward dreams. (This is an automatically generated summary.)
HTML file
Wikipedia page about this book: https://en.wikipedia.org/wiki/Don_Quixote
Release date is 2004-06-01
Produced by David Widger
Keywords: Spain -- Social life and customs -- 16th century -- Fiction; Knights and knighthood -- Spain -- Fiction; Picaresque literature; Romances